PENERAPAN STRATEGI POLITENESS BROWN DAN LEVINSON DALAM KONFLIK CERPEN PERSIMPANGAN KARYA RADITYA DIKA - Nensilianti Nensilianti; Ridwan; Nurhidayah Aprilia Nuna nk (ASMARALOKA : Jurnal Bidang Pendidikan, Linguistik dan Sastra Indonesia, 2026)
This study explores the politeness methods described by Brown and Levinson (1987) in dealing with emotional conflict in the short story "Persimpangan" by Raditya Dika (2023). The main objective of this study is to analyze face-threatening acts (FTAs), positive face (the desire to empathize), negative face (freedom without interference), and various FTA strategies (direct, positive politeness, negative politeness, indirect) that emerge in the interaction between Indah and Ardi. The findings of this study reveal a sociolinguistic irony while methods of maintaining social face may be successful, they lead to the loss of the "face of happiness" over a longer period of time (Indah experiences severe trauma, while Ardi experiences freedom but is trapped in a state of sorrowful regret).